Chlorogenic acid in preventing and curing ultraviolet-induced damage in human skin fibroblast as an antiaging cell model - Ermi Girsang; I Nyoman Ehrich Lister; Chrismis Novilda Ginting; Wahyu Widowati; Seila Arumwardana; Meganita Marthania; Rizal Rizal (Pharmaciana, 2023)
Continuous ultraviolet (UV) irradiation stimulates the over-production of reactive oxygen species (ROS) to cause degenerative diseases. Chlorogenic acid (CA) is found as plants antioxidant that promises medicinal effects. This study examined CA protection against UV-damage in human skin fibroblast (BJ) cells both for curative and preventive therapy. BJ cells were exposed to UV radiation and the addition of CA (6.26-100 mikro g/mL) by preventive and curative addition methods. The cells viability analysis was conducted employing MTS (3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxy-phenyl)-2-(4-sulfophenyl)-2H-tetrazolium) assay. CA treatment before UV exposure exhibited an increased percentage of viability cells than the positive control. In detail, the series of CA concentration (6.25, 12.5, and 25 mikro g/mL) significantly enhanced the percentage of viable cells. The addition of CA after UV exposure denoted the same results. Furthermore, the lower CA concentrations used, the higher cell viability resulted. CA at dose 6.25 mikro g/mL showed the highest viability in cells, while CA 100 mikro g/mL resulted in the lowest viability. In short, CA can preserve and treat cells from UV exposure. The outcome suggested prevention and curative on UV-induced BJ cells, and the tested concentration is applicable for further experiments.